Lack of hemodynamic interaction between CGRP-receptor antagonist telcagepant (MK-0974) and sumatriptan: Results from a randomized study in patients with migraine. (December 2013) - Depré, M; MacLeod, C; Palcza, J; Behm, MO; de Lepeleire, I; Han, T; Panebianco, D; Smith, WB; Blanchard, R; Chodakewitz, JA; Murphy, MG; de Hoon, JN
Objective: The objective of this article is to assess the effects of sumatriptan monotherapy, telcagepant monotherapy, and their combination on blood pressure (BP) in migraine patients during a headache-free period. Methods: A double-blind, placebo-controlled, four-period, single-dose, randomized crossover study in 24 migraine patients was conducted. In each period, patients received a single oral dose of sumatriptan 100 mg alone, telcagepant 600 mg alone, sumatriptan 100 mg coadministered with telcagepant 600 mg, or placebo. Semi-recumbent BP was measured pre-dose and at seven post-dose timepoints over a period of six hours. Individual time-weighted averages in mean arterial pressure (MAP) were evaluated using a linear mixed-effects model. The pharmacokinetics of sumatriptan alone and in the presence of telcagepant were also evaluated using limited sampling times. Results: The mean difference in time-weighted (0–2.5 h) MAP (90% confidence interval) was 1.2 mmHg (−0.2, 2.7) between telcagepant and placebo, 4.0 mmHg (2.5, 5.5) between sumatriptan and placebo, and 1.5 mmHg (0.0, 3.0) between telcagepant with sumatriptan vs sumatriptan alone. When coadministered with telcagepant, the AUC0–6h and Cmax of sumatriptan were increased by 23% and 24%, respectively. The small MAP increases observed after coadministration could possibly be associated with the slight elevations in sumatriptan levels. Conclusion: Telcagepant does not elevate mean MAP, and coadministration of telcagepant with sumatriptan results in elevations in MAP similar to those observed following administration of sumatriptan alone in migraineurs during the interictal period. When coadministered, telcagepant slightly increases the plasma levels of sumatriptan, but without an apparent clinically meaningful effect.